O vínculo afetivo entre professor e as crianças na educação infantil remota - Correa, Sandreise Gomes (Brasil, 2021)
The pandemic caused by the COVID-19 virus has totally changed the routine of people's lives all over the world. The social distance caused by the pandemic also affected education, teaching that used to be face-to-face became remote. This qualitative research addresses the affective relationship between the teacher and children in early childhood education remote teaching. The research aims to investigate how the affective relationship between teacher and children occurred in the remote teaching of early childhood education in public schools in Baixo Amazonas and is based on the authors Wallon (1942, 1995), Vygotsky (1997), Cury (2008) , and in the opinion CNE/CP No. 5/2020. The instrument used for the construction of data were letters sent by teachers and mothers of children in kindergarten, shared through the WhatsApp application. The research included 3 (three) teachers and 2 (two) mothers of children from early childhood education from public schools in two municipalities in Amazonas, from August 5 to September 26, 2021. In this context, it is important to emphasize the relevance from research to professional training, taking into account that affectivity is fundamental in the educational process of the subjects. The research data reveal that affection is central in education and the affective bonds between children-children, teachers - children and their families are of paramount importance in the integral development of students, both in a classroom teaching environment and in a virtual educational environment. In light of this scenario, it is important to state that it is necessary to enhance the relationships of affection between teacher-students, student-students, family-school, whether in face-to-face or remote education.